Breaking dawn - Meyer, Stephenie 1973- (Little Brown and Company, 2008)
Although eighteen-year-old Bella joins the dark but seductive world of the immortals by marrying Edward the vampire, her connection to the powerful werewolf Jacob remains unsevered.